(3eONd JMdjdj s - (3fGLj(B, (3eYdGs; (3QGFa(B, (3Jhajbs ((3YeGf(B:s (3OGQ hGFd ddfTQ(B,s, 2005)
(3ebOeI YGeI aj GdJShjb(B- (3GdHjFI GdJShjbjI(B- (3GdSdhc GdTQGFj(B- (3HMhK GdJShjb hCfXeI GdeYdheGJ(B- (3JLRFI GdShb hGdCShGb GdeSJgOaI(B- (3GdefJLGJ, CfhGYgG hNUGFUgG(B- (3GdJSYjQ hSjGSGJg(B- (3bfhGJ GdJhRjY(B- (3eDSSGJ GdJhRjY(B- (3GdJQhjL hCSGdjHg(B- (3JWhjQ hEHJcGQ GdefJLGJ GdLOjOIs
(3cTGa eUWdMGJ U(B.371s
Keywords: (3COGQI GdeHjYGJs; (3GdEbJUGO GdbjGSjs; (3GdJShjbs